Lithium and osmium isotopes, and trace element ratios in bulk carbonates of different ODP Sites across the Middle Eocene Climatic Optimum - Alexander Krause; Appy Sluijs; Robin Van der Ploeg; Timothy M Lenton; Philip A E Pogge von Strandmann (PANGAEA, 2023)
The Middle Eocene Climatic Optimum (MECO) was a ~400,000-year-long global warming event which occurred ~40 million years ago and interrupted the Eocene extquotesingles long-term cooling trend. We investigated silicate weathering dynamics during the MECO by measuring lithium isotope ratios and elemental ratios (Li/Ca, Al/Ca, Mn/Ca, Sr/Ca, Rb/Ca) from a suite of open-ocean carbonate-rich sediments.